Dok2 mediates the CD200Fc attenuation of A-induced changes in glia. - Lynch, Marina; Downer, Eric (My University, 2012)
Background: The interaction between the membrane glycoprotein, CD200 and its cognate receptor CD200 receptor (CD200R), has been shown to play a role in maintaining microglia in a quiescent state. There is evidence of increased activation under resting and stimulated conditions in microglia prepared from CD200-deficient mice compared with wild-type mice, whereas activation of the receptor by CD200 fusion protein (CD200Fc) ameliorates inflammatory changes which are evident in the central nervous system (CNS) of the mouse model of multiple sclerosis (MS), experimental autoimmune encephalomyelitis (EAE) and also in the hippocampus of aged rats. Additionally, an inverse relationship between microglial activation and expression of CD200 has been observed in animals treated with lipopolysaccharide (LPS) or amyloid- ? (A ? ). Methods: We assessed the effect of CD200R activation by CD200Fc on A ? -induced production of the pro- inflammatory cytokines, interleukin-1 ? (IL-1 ? ) and tumor necrosis factor- ? (TNF ? ) and the expression of microglial activation markers, CD68 and CD40 in cultured glia. The role played by downstream of tyrosine kinase 2 (Dok2) phosphorylation in mediating the effects of CD200R activation was evaluated by siRNA knockdown of Dok2. To further examine the impact of inflammatory changes on synaptic plasticity, the effect of CD200Fc on A ? -induced impairment of long-term potentiation (LTP) in the CA1 region of hippocampal slices was also investigated. Results: We demonstrate that A ? -induced increases in IL-1 ? , TNF ? , CD68 and CD40 were inhibited by CD200Fc. The evidence suggests that Dok2 phosphorylation is a key factor in mediating the effect of CD200Fc, since Dok2 knockdown by siRNA abrogated its effects on microglial activation and inflammatory cytokine production. Consistent with evidence that inflammatory changes negatively impact on LTP, we show that the A ? -induced impairment of LTP was attenuated by CD200Fc. Conclusions: The findings suggest that activation of CD200R and Dok2 is a valuable strategy for modulating microglial activation and may have therapeutic potential in neurodegenerative conditions.
PUBLISHED
Keywords: A ? , CD200, Cytokines, Microglia, siRNA, Dok2, Phagocytosis; A ? , CD200, Cytokines, Microglia, siRNA, Dok2, Phagocytosis